Influence of Instructional Materials Usage on Academic Performance in Secondary Schools in Webuye West Sub-County, Bungoma County - Musuluve Mimo Lilian,; Dr. Ronald Werunga Kikechi, (IJRDO- Journal of Educational Research, 2020)
It emerges that most parents in Webuye West Sub-County, Bungoma County are poor and therefore unable to meet their cost-sharing part. Consequently, their children lack some of the basic instructional materials. As a result the study seeks to find out the influence of the selection of these materials on the academic performance of secondary schools in Webuye West Sub-County, Bungoma County. The study employed the education production function (EPF) as its theoretical framework. This (EPF) postulates that inputs determine the output of an education system. The research design adopted in this study was descriptive survey in which the researchers went in the field to collect data directly. The target population in this study was school principals, teachers, and students. Webuye West Sub-County, Bungoma County has a total of 36 public secondary schools, 36 principals, 340 teachers and 5230 students. The sample size in this study was 11 secondary schools, which were selected through simple random technique; 16 principals who were purposively selected from the sampled schools; 102 teachers who were purposively selected from the sampled schools, and 1569 students randomly selected from the sampled schools. Data collection involved the use of questionnaires, interview and document analysis. The analysis of data in this study was descriptive in nature. Data is presented in tables with emphasis to frequencies and percentages. Students in schools where resource shortages made minimal impact on instruction, according to their principals, had similar academic achievement to students in schools where principals felt that resource shortages made a moderate impact on instruction. The pattern of little difference in achievement, although not observed across all countries, was observed in many of the high-performing and English-speaking countries. As with academic, the effect resource shortages had on a school’s capacity to provide education in Bungoma West Sub-County varied across decile groupings and school sizes, but in contrast with academic, there were no variations when major urban schools were compared to schools in other locations.